Increasing the Production Capacity of Mozzarella Cheese as a Pioneer for the Cheese Village at KU Mustarika Jaya Makmur, Ngantang - Irfin, Zakijah; Rachmawati, Diana; Moentamaria, Dwina; Rulianah, Sri; Dwi Chrisnandari, Rosita; Akhsanu Takwim, R.N. (PELITA NUSA TENGGARA, 2025)
Indonesia has significant potential in dairy cattle production, one example being in Dusun Tepus, Ngantru Village, Ngantang Subdistrict, Malang Regency. The business group “Mustarika Jaya Makmur” consists of dairy farmers producing fresh milk. Previously, the State Polytechnic of Malang (Polinema) provided solutions in the form of training on supply chain management, milk processing, and the application of production calculation tools to support efficiency. Considering the business potential of mozzarella cheese, the group increased its production capacity to 50 liters of fresh milk on a pilot scale to initiate the “Kampung Kedju” program, aimed at improving the villagers’ livelihoods. This Community Service Program (PPM) is expected to provide solutions through production enhancement, assistance in the use of equipment in accordance with standard operating procedures (SOP), and the implementation of Good Manufacturing Practices (GMP) in cheese production. The expected outputs include improved partner capacity, scientific publications, and copyright registration of a HACCP guideline.